2002
DOI: 10.1128/jvi.76.11.5822-5828.2002
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Spectra of Herpes Simplex Virus Type 1 Thymidine Kinase Mutants

Abstract: To examine whether the exonuclease activity intrinsic to the polymerase (Pol) of herpes simplex virus type 1 can influence the mutational spectra, we applied the denaturing gradient gel electrophoresis (DGGE) system combined with sequencing to characterize thymidine kinase mutants isolated from both the wild-type virus and a mutant deficient in exonuclease activity, Y7. Wild-type viruses produced predominately frameshift mutations (67%), whereas Y7 replicated a significantly lower proportion of frameshifts (21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…These results suggested that HSV-1 Pol could preferentially misinsert nucleotides at these positions that were subsequently proofread by the intrinsic exonuclease activity. Conversely, different types of substitutions identified at other locations among wild-type and Y7 Pol-induced mutants suggest that Y7 Pol might possess an altered polymerase activity, consistent with a recent study of the mutation spectra of tk mutants derived from both wild-type and Y7 Pols (22). This is supported by the fact that Y7 Pol exhibits altered binding affinities for nucleoside analogs (15) and indicates that the exonuclease domain has critical structural and functional roles in the catalytic subunit of the HSV-1 Pol holoenzyme.…”
Section: Discussionsupporting
confidence: 54%
“…These results suggested that HSV-1 Pol could preferentially misinsert nucleotides at these positions that were subsequently proofread by the intrinsic exonuclease activity. Conversely, different types of substitutions identified at other locations among wild-type and Y7 Pol-induced mutants suggest that Y7 Pol might possess an altered polymerase activity, consistent with a recent study of the mutation spectra of tk mutants derived from both wild-type and Y7 Pols (22). This is supported by the fact that Y7 Pol exhibits altered binding affinities for nucleoside analogs (15) and indicates that the exonuclease domain has critical structural and functional roles in the catalytic subunit of the HSV-1 Pol holoenzyme.…”
Section: Discussionsupporting
confidence: 54%
“…That study (13) reported that selectivity of correct over incorrect dNTP was ϳ300, whereas bacteriophage T4 and T7 DNA polymerases discriminate among dNTPs by a factor of Ͼ1000 and Ͼ100,000, respectively (14 -16). Previous studies suggested that the exo activity of HSV-1 pol contributes substantially to the fidelity of HSV replication in vivo, because mutation of the conserved exo site III of the HSV-1 pol catalytic subunit was associated with a strong mutator phenotype (10,17,18). Moreover, such pol mutants are genetically unstable and revert or recombine with high frequency (10), suggesting strong in vivo selection against an HSV-1 pol lacking exo activity.…”
mentioning
confidence: 99%
“…Furthermore, the Y577H mutation not only loses exonuclease activity but also alters the polymerase activity as it replicates misinsertions at positions distinct from those of wild-type Pol. Only 3 identical base substitutions are found among 15 and 52 tk mutations replicated by wild-type and exonuclease negative Pol, respectively (Lu, Hwang, and Hwang, 2002b). Theoretically, one would expect to observe more identical substitutions in both groups if the exonuclease Pol does not have altered polymerase activity.…”
Section: Exonuclease Deficient Polymerase Induces Altered Mutation Spmentioning
confidence: 97%
“…In contrast, the Y7 recombinant virus, which contains the Y577H mutation in the Exo III motif, replicates the tk gene with significantly less frameshift mutations (21%; p < 0.005) relative to wild-type virus (Lu, Hwang, and Hwang, 2002b). Furthermore, although the majority of substitutions are transitional changes in mutants derived from both wild-type and exonuclease-deficient viruses, they distribute differently (Lu, Hwang, and Hwang, 2002b). These findings imply that HSV Pol can incorporate mispaired nucleotides, and most of the misinsertions are corrected by the proofreading activity during DNA synthesis.…”
Section: Exonuclease Deficient Polymerase Induces Altered Mutation Spmentioning
confidence: 99%
See 1 more Smart Citation